2010
DOI: 10.1016/j.jala.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Fully Automated High-Throughput Phototransfection System

Abstract: W e have designed and implemented a framework for creating a fully automated high-throughput phototransfection system. Integrated image processing, laser target position calculation, and stage movements show a throughput increase of O23Â over the current manual phototransfection method although the potential for even greater throughput improvements (O110Â) is described. A software tool for automated off-line singlecell morphological measurements, as well as real-time image segmentation analysis, has also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It would be possible to apply a more elaborate cell-recognition algorithm that, for example, determines the entire cell shape and marks precisely the desired number of target positions on that cell as described in Ref. 20 . However, concerning how different samples should be treated, there can be numerous variables and inconsistences as a result of different cell types, shapes as well as confluence and illumination conditions; making such an algorithm inherently complex and time consuming.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be possible to apply a more elaborate cell-recognition algorithm that, for example, determines the entire cell shape and marks precisely the desired number of target positions on that cell as described in Ref. 20 . However, concerning how different samples should be treated, there can be numerous variables and inconsistences as a result of different cell types, shapes as well as confluence and illumination conditions; making such an algorithm inherently complex and time consuming.…”
Section: Methodsmentioning
confidence: 99%
“…This process is tedious, time-consuming and while enabling to address individual cells which make single-cell studies possible, only a small number of cells can actually be targeted per procedure. The number of addressable cells for manual laser optoporation reported with different setups varies approximately between 20 and about 1000 cells per hour 9 17 20 . Another hurdle posed for automating the procedure is the necessary optimization of several parameters such as exposure time, laser power and optimal location of irradiation for specific cell lines or experimental setups which can be time consuming as well and may have to be repeated between experiments 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With image processing, the location of the individual cells can be determined. In combination with an auto-focus system to control the axial position of the photoporation laser beam, this allows cells to be photoporated in an automated fashion [107,108]. In one example, it was demonstrated that ~300 cells/min can be photoporated that way [107].…”
Section: Experimental Procedures For Direct Laser-induced Photoporationmentioning
confidence: 99%
“…In the arena of custom-built systems, the open source Micropilot [10] has indeed given scientists the ability to run automated FRAP assays using training sets to study complex biological questions. Other systems have also capitalized on homebuilt and programmable microscopes to process cells for other advanced optical experiments such as optoporation [11,12]. Although these systems are allowing scientists to run more advanced experiments without supervision, they lack the ability to deliver small molecules or proteins at predefined timepoints.…”
Section: Introductionmentioning
confidence: 99%